Just like my dad - Gardella, Tricia; Apple, Margot ([New York, NY] : HarperCollins, 1993)
A young child glories in the sights, sounds, smells, and activities of a day spent working on a cattle ranch as a cowhand, just like Dad.
2.4
K-3
K-3
Book Links (A.L.A.)
Library Talk
780
Keywords: Ranch life -- Fiction; Father and child -- Fiction; Ranch life -- Fiction; Father and child -- Fiction